Familial Interstitial Lung Disease Caused by Mutation of the STING1 Gene - Li, Jinying; An, Shuhua; Du, Zhongdong (Frontiers in Pediatrics, 2020)
Mutations that affect STING1（TMEM173）gene cause an rare diseases of autoinflammatory syndrome ，which is known as the STING-associated vasculopathy with onset in infancy (SAVI) initially described in 2014[1]. Thus far，only four reports have been conducted regarding families affected with SAVI in the literature .In this article, the clinical, laboratory and genetic characteristics of a two generation of three cases of SAVI is described. Unlike previously reported cases that were caused by STING1 mutation，the initial and major clinical manifestations of the mentioned cases are largely identified in the lungs with interstitial lung disease (ILD)，while the evidence of typical extrapulmonary symptoms of early-onset systemic inflammation (e.g.cutaneous vasculopathy) were minimal except for the proband diagnosed with arthritis 8 years after onset. Besides，the younger one even showed no symptoms.The report expanded the phenotypic spectrum related to mutations in STING1.The proband was examined with bronchoscopy ，alveolar lavage and examination were performed to determine the cause.This study emphasizes that in the clinical assessment of interstitial pneumonia in children, furthermore, the possibility of STING1 mutation should be considered ,especially of patients plus with arthritis.